Liquid‐to‐solid ratio control as an advanced process control solution for continuous twin‐screw wet granulation. Issue 7 (30th March 2018) - Nicolaï, Niels; De Leersnyder, Fien; Copot, Dana; Stock, Michiel; Ionescu, Clara M.; Gernaey, Krist V.; Nopens, Ingmar; De Beer, Thomas
Abstract : Assuring compliance of intermediate and final quality attributes in a continuous pharmaceutical manufacturing campaign is of utmost importance. Application of corrective actions might be required in real‐time. This work exemplifies the steps needed to identify a linear pulse transfer function for the dynamic behavior of the granule liquid‐to‐solid ratio (%w/w) at the end of the granulation unit of a commercial ConsiGma TM ‐25 production line. Near‐infrared spectroscopy was used to monitor the granule composition in‐line. The outcome for both the tracking and regulator problem using either conventional or model predictive control was implemented and evaluated. Dynamic setpoints were correctly followed and an RMSE of 0.25%w/w with respect to the setpoint was obtained when inducing artificial disturbances. Important practical challenges were also tackled. Examples are fouling, computational limitations, and the limited flexibility of the automation software. Applying the proposed advanced process control solution offers an answer to upstream material flow rate deviations. © 2018 American Institute of Chemical Engineers AIChE J, 64: 2500–2514, 2018